The Mimicry of Identity: A Visual Semiotic Analysis and Pattern Recognition of City Branding in Indonesia - Prawira, Nanang Ganda; Prawira, Mega Fitriani Adiwarna (Integrasi Sains Media, 2025)
In the era of regional autonomy, Indonesian jurisdictions are increasingly racing to articulate distinct promotional identities to compete for global capital and tourism. However, this pursuit of distinction often yields a landscape of visual conformity. This study investigates the visual DNA of N=13 purposively selected, officially verified promotional brands to understand the structural forces behind this homogenization, explicitly excluding administrative heraldry to resolve the issue of categorical conflation. Employing a multi-method qualitative approach, the research combines Visual Content Analysis (VCA) with a three-stage Social Semiotic protocol (denotation, connotation, and myth) adapted from Roland Barthes. The findings reveal a significant paradox: while ethnic markers are utilized to signal authenticity, they are predominantly framed within a Global Modernist shell. This is characterized by the overwhelming dominance of English-language slogans (76.9%) and standardized sans-serif typography (84.6%). The analysis unmasks the Myth of Uniqueness, demonstrating that the branding process is governed by mimetic isomorphism—a bureaucratic reflex to imitate successful peers to secure institutional legitimacy. Consequently, local heritage is often reduced to a commodified ornament, leading to identity drift and a dilution of the city’s Unique Selling Proposition (USP). The study concludes that to break the cycle of visual mimicry, municipal governance must shift from top-down administrative projects to participatory, narrative-centric brand management. The research introduces Semiotic Due Diligence as a strategic requirement for developing authentic and resilient place brands in emerging economies.